Hideyoshi and Rikyū - Nogami, Yaeko, 1885-1985 (University of Hawai' i Press, 2018)
"Nogami Yaeko's compelling novel of political intrigue in sixteenth-century Japan depicts the intertwined lives of two iconic historical figures. Toyotomi Hideyoshi rose through the ranks from a common foot soldier to become the military ruler of Japan but struggled to win respect among the cultured nobility. He found both a friend and an invaluable political advisor in Sen no Rikyū, Japan's most respected tea master. A wealthy merchant in his own right, Rikyū's talent for tea ceremony propelled him into the ruler's court. Deftly balancing Hideyoshi's love of ostentatious display with the ideals of simplicity and rusticity embodied in the way of tea, Rikyū commands respect from loyal students and court nobles alike"--Amazon.com